Enhanced protein encapsulation in polymer vesicles with hydrophobic membrane-anchor peptides - Mertz, Michael (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2022)

Enzymatic Synthesis of Sialic Acids in Microfluidics to Overcome Cross-Inhibitions and Substrate Supply Limitations - Obst, Franziska; Mertz, Michael; Mehner, Philipp J.; Beck, Anthony; Castiglione, Kathrin; Richter, Andreas; Voit, Brigitte; Appelhans, Dietmar (ACS Applied Materials and Interfaces, 2021)
Multienzymatic cascade reactions are a powerful strategy for straightforward and highly specific synthesis of complex materials, such as active substances in drugs. Cross-inhibitions and incompatible reaction steps, however, often limit enzymatic activity and thus the conversion. Such limitations occur, e.g., in the enzymatic synthesis of the biologically active sialic acid cytidine monophosphate N-acetylneuraminic acid (CMP-Neu5Ac). We addressed this challenge by developing a confinement and compartmentalization concept of hydrogel-immobilized enzymes for improving the efficiency of the enzyme cascade reaction. The three enzymes required for the synthesis of CMP-Neu5Ac, namely, N-acyl-d-glucosamine 2-epimerase (AGE), N-acetylneuraminate lyase (NAL), and CMP-sialic acid synthetase (CSS), were immobilized into bulk hydrogels and microstructured hydrogel-enzyme-dot arrays, which were then integrated into microfluidic devices. To overcome the cytidine triphosphate (CTP) cross-inhibition of AGE and NAL, only a low CTP concentration was applied and continuously conveyed through the device. In a second approach, the enzymes were compartmentalized in separate reaction chambers of the microfluidic device to completely avoid cross-inhibitions and enable the use of higher substrate concentrations. Immobilization efficiencies of up to 25% and pronounced long-term activity of the immobilized enzymes for several weeks were realized. Moreover, immobilized enzymes were less sensitive to inhibition and the substrate-channeling effect between immobilized enzymes promoted the overall conversion in the trienzymatic cascade reaction. Based on this, CMP-Neu5Ac was successfully synthesized by immobilized enzymes in noncompartmentalized and compartmentalized microfluidic devices. This study demonstrates the high potential of immobilizing enzymes in (compartmentalized) microfluidic devices to perform multienzymatic cascade reactions despite cross-inhibitions under continuous flow conditions. Due to the ease of enzyme immobilization in hydrogels, this concept is likely applicable for many cascade reactions with or without cross-inhibition characteristics.
CRIS-Team Scopus Importer:2021-11-05
Keywords: biocatalysis; cascade reaction; compartmentalization; enzyme immobilization; incompatibility; microfluidic reactor; microstructured hydrogel; sialic acid

Fast and effective chromatographic separation of polymersomes from proteins by multimodal chromatography - Mertz, Michael; Golombek, Florian; Boye, Susanne; Moreno, Silvia; Castiglione, Kathrin (Journal of Chromatography B-Analytical Technologies in the Biomedical and Life Sciences, 2021)
Artificial vesicles made of block copolymers, so-called polymersomes, represent a versatile chassis for the creation of functionalized nanocompartments with a wide range of biotechnological applications. The specific application depends on the biomolecules – usually proteins – that are positioned in the interior, in the membrane or on the surface of the vesicles. However, not all added proteins are integrated into the vesicles during the usual manufacturing processes of polymersomes. Excess proteins must therefore be removed. The separation techniques currently used for this, however, are associated with decisive disadvantages, such as damaged vesicles, long process times, or small sample volumes that can be processed. To overcome these drawbacks, we investigated the applicability of Capto™ Core 700 resin for polymersome purification. Polymersomes were not damaged or otherwise affected by passage through the column verified by hollow fiber flow field flow fractionation technique. Using three proteins with divergent physico-chemical properties as examples, it was demonstrated that different types of unentrapped proteins were efficiently removed from polymersome dispersions. The dynamic binding capacities in the presence of polymersomes varied between 9.5 and 16.5 mg per mL resin for the proteins applied. The technique can be used for small and large sample volumes alike. In addition, it can be used without special laboratory equipment. This adds a new and easy-to-use purification method for polymer vesicles to the repertoire that will also facilitate the large-scale production of functionalized polymersomes.
CRIS-Team Scopus Importer:2021-01-08
Keywords: Multimodal chromatography; Negative purification; Polymer vesicle; Polymersome; Protein separation

Increased protein encapsulation in polymersomes with hydrophobic membrane anchoring peptides in a scalable process - Mertz, Michael; Castiglione, Kathrin (International Journal of Molecular Sciences, 2021)
Hollow vesicles made from a single or double layer of block-copolymer molecules, called polymersomes, represent an important technological platform for new developments in nano-medicine and nano-biotechnology. A central aspect in creating functional polymersomes is their combination with proteins, especially through encapsulation in the inner cavity of the vesicles. When producing polymersomes by techniques such as film rehydration, significant proportions of the proteins used are trapped in the vesicle lumen, resulting in high encapsulation efficiencies. However, because of the difficulty of scaling up, such methods are limited to laboratory experiments and are not suitable for industrial scale production. Recently, we developed a scalable polymersome production process in stirred-tank reactors, but the statistical encapsulation of proteins resulted in fairly low encapsulation efficiencies of around 0.5%. To increase encapsulation in this process, proteins were genetically fused with hydrophobic membrane anchoring peptides. This resulted in encapsulation efficiencies of up to 25.68%. Since proteins are deposited on the outside and inside of the polymer membrane in this process, two methods for the targeted removal of protein domains by proteolysis with tobacco etch virus protease and intein splicing were evaluated. This study demonstrates the proof-of-principle for production of protein-functionalized polymersomes in a scalable process.
CRIS-Team Scopus Importer:2021-07-09
Keywords: Functionalization; Hydrophobic peptide; Polymer vesicle; Polymersome; Protein encapsulation